The politics of tradition folk healing on two continents, Part II. - Cassell McEntire Nancy; International Society for Ethnology and Folklore : Working group on the ritual year : annual conference (9.) (2013) (Szeged) (2014)
The practice of folk healing seems implausible in today’s world, especially as we rely increasingly on new medicines and technologies to cure us from afflictions. Yet even within a modern, Westernized setting, traditional healing rituals do persist, sustained by personal testimonials, and passed from person to person. as they continue, these rituals maintain an important role in their communities. this article continues an investigation of healing traditions in collaboration with Marlene Hugoson, of Uppsala, Sweden. My fieldwork, in rural Illinois, USA, draws on interviews with Pat Rhoads, the owner of a local restaurant. in her spare time, Pat uses a prayer and a ritual that she learned from her grandfather, Ernest Marvin, to heal afflicted children at the base of a large oak, known as “the asthma tree”. she also has applied the same prayer to cure warts, and she tells how similar rituals can mitigate the pain of contact with fire or intense heat, a process known as “blowing out a burn”. Despite the fact that such cures are uncommon, Pat continues to practice them. furthermore, she is strengthened by her success, which she sees as a validation of her Christian faith.
Keywords: Orvos- és egészségtudomány; Társadalomtudományok; Szociológia